The Development of the Student Book Five Phase Learning Model by Van Hiele on 2D material in Class VIII SMP Laboratorium, State University of Malang - Sugiyarti Sugiyarti (Universitas Negeri Malang, 2014)
Pengembangan Buku Siswa dengan Mengacu Lima Fase Belajar Model Van Hiele pada Materi Bangun Ruang Sisi Datar Kelas VIII SMP Laboratorium Universitas Negeri Malang Abstract: The aim of this study is the development of the student produces books and lesson plan (RPP), which is characterized by a phase of learning models by  Van Hiele the 2D materials on class VIII are valid, practical and effective.The  Development model used was developed by Plomp (2010). The average score for all aspects of student book validation results, RPP and final tests valid criteria. The average score for all indicators observations feasibility and feasibility study books students meet practical criteria. Mastery of geometry is measured through the final test results and the results of the activity of student performance in achieving mastery of classical books exceeds the 87% stipulated classical mastery of 70%. The observation of student activity during learning for all indicators meet the criteria set very high student activity. Students' response to the book and learning the learning phase model of van Hiele on the material of figures with the flat side positive. Notes, suggestions and comments from both validators, practitioners and observers are used in revising the development of this product. Results of the validation and field trials obtained student books and lesson plan (RPP) valid, practical and effective. Key Words: geometry flat side, the learning phase model of Van Hiele Abstrak: Penelitian pengembangan ini bertujuan menghasilkan buku siswa dan rencana pelaksanaan pembelajaran (RPP) yang bercirikan fase belajar model van Hiele pada materi bangun ruang kelas VIII yang valid, praktis dan efektif. Model pengembangan yang digunakan dikembangkan oleh Plomp (2010). Skor rata-rata untuk semua aspek hasil validasi buku siswa, RPP dan tes akhir memenuhi kriteria valid. Skor rata-rata untuk semua indikator hasil pengamatan keterlaksanaan pembelajaran dan keterlaksanaan buku siswa memenuhi kriteria praktis.  Penguasaan materi bangun ruang yang diukur melalui hasil tes akhir dan hasil aktivitas unjuk kerja siswa dalam buku mencapai penguasaan klasikal 87% melebihi penguasaan klasikal yang ditetapkan yakni 70%. Hasil pengamatan aktivitas siswa selama pembelajaran untuk semua indikator memenuhi kriteria yang ditetapkan yakni aktivitas siswa sangat tinggi. Respon siswa terhadap buku dan pembelajaran dengan fase belajar model van Hiele pada  materi bangun ruang sisi datar positif. Catatan, saran dan komentar baik dari validator, praktisi dan observer digunakan dalam merevisi produk pengembangan ini. Hasil validasi dan uji coba lapangan diperoleh buku siswa dan rencana pelaksanaan pembelajaran (RPP) yang valid, praktis dan efektif.  Kata kunci: bangun ruang sisi datar, fase belajar model Van Hiele